Influencia de la comunicación entre usuarias en la participación de las actividades del círculo del adulto mayor Pacasmayo – provincia de Pacasmayo: 2017. - Díaz Saldaña, Ana Lucy (2018)
This thesis was carried out with the aim to explain the influence of the communication between users influences the participation of the activities of the Circle of the Older Adult Pacasmayo - Pacasmayo Province: 2017. It has been considered the type of applied research, on the basis of an explanatory design, has applied the methods and techniques of quantitative and qualitative research, the sample consisted of 108 users of the program of the older adult. The results obtained in the investigation, it can be deduced that present low level of communication, formation of subgroups and presence of conflicts between users that generates low participation in the activities programd by the circle of the Older Adult Pacasmayo. With this research, we intend to provide information, to implement programs directed to the families and institutions benefactors to seek a solution to this social problem. As social workers, we must promote an excellent quality of life through a process of aging healthy and happy.